Renegotiating the periphery: Oil discovery, devolution, and political contestation in Kenya. Issue 1 (January 2019) - Orr, David W.
Highlights: Devolution is fundamentally changing Kenya's political structure. Post-devolution, there is greater acknowledgement of peripheral voices. Since oil's discovery and devolution, new 'layers' of conflict have emerged. Politicians in devolved regions position themselves relative to the oil discovery. Devolution is a double-edged sword to mitigate political instability in Kenya. Abstract: Devolution in Kenya was introduced in 2013 as a means towards more participatory and responsive government. Yet in the first five years of its implementation, the unpredictability and complexities of what devolution means in practice have become increasingly apparent. The distribution of natural resources forms a key point of contention, brought sharply to the fore in the historically marginalised Turkana region of Kenya, where devolution has coincided with oil discovery. This paper examines the emergent power contestations around oil discovery at the core-periphery (national-county), corporate-periphery (oil firm-county) and intra-periphery (within the county) levels in Turkana. It argues that devolution has been a double-edged sword to mitigate political instability in Turkana County. Indeed, the stability of Kenya, and particularly Turkana, is being defined through new forms of contestation and renegotiation since the discovery of oil and the implementation of a devolution process. Whilst devolution has illuminated county-level grievances and enabled material redistribution to peripheral regions from the national government to an extent that would have been improbable in the pre-devolution era, it risks empowering rent-seeking politicians to construct new conflicts and foment intra-county divisions in a bid to secure access to oil-related windfalls.